Repeated Inoculation of Young Calves With Rumen Microbiota Does Not Significantly Modulate the Rumen Prokaryotic Microbiota Consistently but Decreases Diarrhea - Bu, Dengpan; Zhang, Xin; Ma, Lu; Park, Tansol; Wang, Lingling; Wang, Mengzhi; Xu, Jianchu; Yu, Zhongtang (Frontiers in Microbiology, 2020)
The complex rumen microbiota exhibits some degree of host specificity. The undeveloped simple rumen microbiota is hypothetically more amendable. The objective of this study was to investigate if the rumen prokaryotic microbial assemblage of young calves can be reprogrammed by oral inoculation with rumen microbiota of adult cows. Twenty newborn male calves were randomly assigned to four groups (n = 5 per group), with two groups being orally inoculated with rumen microbiota (fresh rumen fluid) collected from two lactating dairy cows, while the other two groups receiving autoclaved rumen fluid collected from another two donor cows. Each calf was orally drenched with 100, 200, 300, 400, and 500 mL of the rumen fluid at d3, d7, d21, d42, and d50, respectively, after birth. The inoculation with rumen microbiota did not affect (P > 0.05) feed intake, average daily gain (ADG), heart girth, or feed conversion ratio but significantly (P < 0.01) lowered instance of diarrhea. At the age of 77 days (27 days post-weaning), all the calves were slaughtered for the sampling of rumen content and determination of empty rumen weight. Rumen fermentation characteristics were not affected (P > 0.05) by the inoculation. Rumen prokaryotic microbiota analysis using metataxonomics (targeting the V4 region of the 16S rRNA genes) showed that the calf rumen prokaryotic microbiota differed from that of the donors. Two Succinivibrionaceae OTUs, two Prevotella OTUs, and one Succiniclasticum OTU were predominant (relative abundance > 2%) in the donors, but only one Succinivibrionaceae OTU was found in the calves. On the other hand, five other Prevotella OTUs were predominant (>3%) in the calves, but none of them was a major OTU in the donors. No correlation was observed in relative abundance of major OTUs or genera between the donor and the calves. Principal coordinates analysis (PCoA) based on weighted UniFrac distance showed no significant (P > 0.05) difference in the overall rumen prokaryotic microbiota profiles among the four calf groups, and principal component analysis (PCA) based on Bray-Curtis dissimilarity showed no significant (P > 0.05) difference in functional features predicted from the detected taxa. Nor the calf rumen microbiota showed any clustering with their donor’s. Repeated oral inoculation with rumen microbiota probably has a limited effect on the development of rumen microbiota, and the rumen microbiota seems to develop following a program determined by the host and other factors.